Discordant retention of HIV-infected mothers and children: Evidence for a family-based approach from Southern Mozambique. Issue 32 (7th August 2020) - Nhampossa, Tacilta; Fernandez, Sheila; Augusto, Orvalho; Fuente-Soro, Laura; Maculuve, S.ó.nia; Bernardo, Edson; Saura, Anna; Casellas, Aina; Gonzalez, Raquel; Ruperez, Maria; Karajeans, Esmeralda; Vaz, Paula; et al.
Abstract : Abstract: It is often assumed that children and their caregivers either stay in care together or discontinue together, but data is lacking on caregiver–child retention concordance. We sought to describe the pattern of care among a cohort of human immunodeficiency virus (HIV) infected children and mothers enrolled in care at the Manhiça District Hospital (MDH). This was a retrospective review of routine HIV clinical data collected under a larger prospective HIV cohort study at MDH. Children enrolling HIV care from January 2013 to November 2016 were identified and matched to their mother's HIV clinical data. Retention in care for mothers and children was assessed at 24 months after the child's enrolment. Multinomial logistic regression was performed to evaluate variables associated with retention discordance. For the 351 mother–child pairs included in the study, only 39% of mothers had concordant care status at baseline (23% already active in care, 16% initiated care concurrently with their children). At 24-months follow up, a total of 108 (31%) mother–child pairs were concordantly retained in care, 88 (26%) pairs were concordantly lost to follow up (LTFU), and 149 (43%) had discordant retention. Pairs with concurrent registration had a higher probability of being concordantly retained in care. Children who presented with advanced clinical or immunological stage had increased probability of being concordantly LTFU. High rates of LTFU as well as high proportions of discordant retention among mother–child pairs were found. Prioritization of a family-based care model that has the potential to improve retention for children and caregivers is recommended.